Uncertainty From the Perspective of Geography Education: A Systematic Review - Hanke, Melissa; Paseka, Angelika; Sprenger, Sandra (Journal of Geography Education, 2022)
The aim of the paper is to present an overview of definitions and concepts of uncertainty in the context of geography education, that have been published in German and English papers. For this purpose, a systematic review was conducted. The selected papers (n=64) were analyzed by qualitative content analysis. It becomes evident that in the majority of the papers no explicit definitions of the term ‘uncertainty’ is available, however, references to other authors as well as implicit references occur. Science-, knowledge-, and action-oriented approaches and references to different categories (e.g. actor group and time) can be differentiated.
Keywords: uncertainty, geography education, education for sustainable development, systematic review